Socialization and Assistance Program Patnership Parents, School and Societies involvement In Early Childhood Education - Jeti, La; Manan, Manan; Putra, L.M Ricard Zeldi; Asnawati, Asnawati; Muliati, Muliati (Aulad: Journal on Early Childhood, 2021)
This service aims to socialize and assist the partnership program of parents, schools, and the community in involvement in the implementation of early childhood education, as mandated by the Minister of Education and Culture No. 30 of 2017 concerning Family Involvement in Education. This activity was carried out in Lawela Village, South Buton Regency. This service activity consists of 3 stages. The first stage is the Community Service Team together with parents, schools and communities to carry out FGD (Forum Group Discussion) to socialize the partnership program. The second stage is partnership assistance to families, schools and communities. Third Stage The Service Team conducts interviews and observations to parents, teachers and the community regarding involvement in children's education at the Lawela Village Kindergarten. The results of this service show that through the socialization and assistance of the partnership program, a partnership relationship is built between parents, schools and the community, towards the implementation of early childhood education. These three elements of education are mutually involved in parenting programs, building communication for early childhood education, learning activities at home, and joint decision making.